Pack of lies the advertising of tobacco - Jhally, Sut; Kilbourne, Jean; Pollay, Rick; Foundation for Media Education ([Northampton, Mass.] : Foundation for Media Education, 1991)
A hard-hitting expose of the advertising strategies of the tobacco industry, revealing the cynical and manipulative way in which the'pack of lies' is spread, and new generations of nicotine addicts are created
Title from title screen
Director of photography, Boyd Estus ; sound recordist, John Dildine ; graphics, Frank Verni, Liz O'Rourke, Chris Bernazzani
Featuring: Jean Kilbourne, Rick Pollay
Keywords: Advertising -- Tobacco -- United States; Tobacco Industry